Stimulation of Early Reading Skills through Alphabet Board Media in Slow Learner Children in Inclusive Kindergarten of PAS Baitul Qur'an - Diyah Ayu Ningtiyas; Ida Yeni Rahmawati; Dian Kristiana (EduBasic Journal: Jurnal Pendidikan Dasar, 2022)
This study aimed to describe the application of the alphabet board media to stimulate early reading skills for slow learners. The type of research used was descriptive research with a qualitative approach. It is called descriptive research since it produced case study data in the form of an overview of the application of the alphabet board media in stimulating the early reading skills of slow learner children in Inclusive Kindergarten of PAS Baitul Qur'an. Data collection techniques employed observation, in-depth interviews, and documentation. The subjects in this study were two slow learner children, two teachers, and principals at Inclusive Kindergarten of PAS Baitul Qur'an, with an individual class system of one child and one teacher. From the study results, it can be concluded that applying the alphabet board media could stimulate early reading skills for slow learner children in Inclusive Kindergarten of PAS Baitul Qur'an. The stimulation carried out by the teacher in developing early reading skills included seeing the letters on the alphabet board, listening to the teacher's orders, and following the teacher's orders by reciting the letters on the alphabet board, starting with the vowels first, to the consonants, and then proceed into two syllables, i.e., consonants and vowels, and repeating the words on the alphabet board. This best practice in Inclusive Kindergarten of PAS Baitul Quran can be a reference for teachers who want to solve the problem of slow learning in early childhood.